Deskripsi Hasil Belajar Peserta Didik yang Menggunakan Modul Inkuiri Terbimbing pada Pembelajaran Kimia - Diana Safitri; Iryani Iryani (Universitas Negeri Padang, 2021)
The purpose of the review research is to describe the cognitive learning outcomes of students who use guided inquiry modules in chemistry learning. This type of research is a research library that uses a semi-systematic approach, uses secondary data and uses documentation methods. Content analysis techniques are used in data collection (Snyder, 2019). Guided inquiry modules is effective in increasing the cognitive learning outcomes of students in chemistry learning. Structured arrangement of guided inquiry modules can make students understand learning objectives and concepts clearly. The guided inquiry module which is equipped with multiple representations also makes it easier for students to learn concrete and abstract.